Logic programming and nonmonotonic reasoning 11th International Conference, LPNMR 2011, Vancouver, Canada, May 16-19, 2011. Proceedings - International Conference on Logic Programming and Nonmonotonic Reasoning 2011 Vancouver, Canada); Delgrande, James P.; Faber, Wolfgang; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This volume contains the refereed proceedings of the 11th International Conference on Logic Programming and Nonmonotonic Reasoning, LPNMR 2011, held in May 2011 in Vancouver, Canada. The 16 revised full papers (13 technical papers, 1 application description, and 2 system descriptions) and 26 short papers (16 technical papers, 3 application description, and 7 system descriptions) which were carefully reviewed and selected from numerous submissions, are presented together with 3 invited talks. Being a forum for exchanging ideas on declarative logic programming, nonmonotonic reasoning, and knowledge representation, the conference aims to facilitate interactions between those researchers and practitioners interested in the design and implementation of logic-based programming languages and database systems, and those who work in the area of knowledge representation and nonmonotonic reasoning.
Electronic reproduction.
Keywords: Logic programming -- Congresses; Nonmonotonic reasoning -- Congresses; Electronic books